Redefinisi Jihad Makna Dan Manfaatnya - Sahal afhami sahal (Fakultas Hukum Universitas Darul Ulum, 2016)
Jihad as a holy teachings of Islam which degrades the meaning, there is flow legality abusing Islamic jihad to violence, terrorism, and murder humans illegally. Though the true meaning of jihad is the struggle of all forms of struggle. This research will look for answers to the meaning and benefits of true jihad. The findings produced that jihad was taught Islam is a suggestion and not a goal that Islam teaches not only a form of warfare against the enemy but to fight on all aspects of life that brings people to ignorance, poverty, injustice, and even fight for my family members to do good deeds, and maintain parents. Fight against the enemy is not prohibited, but if the enemy had laid down arms it is no longer advisable to war. While the benefits are for the forgiveness of Allah and success in the life hereafter.